Pengaruh Model Problem Based Learning (PBL) Berbantuan Video Animasi terhadap Kemampuan Berpikir Kritis Peserta Didik SMAN 10 Mataram - Sri Parwati; Muhammad Zuhdi; Syahrial A (Mataram University, 2026)
The low level of students’ critical thinking skills in physics learning remains a common problem. Conventional teacher-centered learning is considered not yet optimal in improving these skills. This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by animated videos on students’ critical thinking skills. This quantitative research employed a quasi-experimental method using a Non-equivalent Control Group Design. The study involved all 55 students of grade XI MIPA at SMAN 10 Mataram. Saturated sampling technique was applied, resulting in class XI MIPA 1 as the experimental class (30 students) and class XI MIPA 2 as the control class (25 students). The experimental class received treatment in the form of the PBL model assisted by animated videos, while the control class was taught using conventional learning methods. The research instrument consisted of an essay test measuring critical thinking skills that had been tested for validity, reliability, difficulty level, and discriminating power. Data analysis techniques included normality test, homogeneity test, t-test, and N-Gain test. The results showed that the average posttest score of the experimental class was 66.67, which was higher than the control class score of 45.06. Hypothesis testing indicated a significance value of 0.02 (p < 0.05), therefore H₀ was rejected. The N-Gain test showed that the improvement in critical thinking skills of the experimental class was categorized as moderate (g = 0.4194), while the control class was categorized as low (g = 0.2525). Thus, the animated video-assisted PBL model was proven to have a significant effect on students’ critical thinking skills, increasing the posttest score by 21.61 points higher than the control class.